Managing Resilience to Change in Merger and Acquisitions - Cristian Dîrvă (Romanian Economic Journal, 2018)
According to numerous studies in the field, the main cause of failure of international mergers and acquisitions is the difficulty of implementing changes requiring the realization of the expected synergies by integrating the acquired company in the case of acquisitions or the two companies merging into the new entity created. Most often, the impediment to successfully completing a merger or an acquisition is employee reluctance to change. Through this study, I propose to analyse the underlying causes of this reaction and potential ways to avoid and/or to overcome it.